''Walk all day'': constructions of gender of children and girls in urban spaces (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
In this article I analyze the meanings of "walk" granted by a group of children with conduct an ethnographic research, with the aim of reconstructing gender practices are agency found in the urban context of the city of Neuquén province, located north of Patagonia Argentina. Specifically, the work aims to visualize how the movements of the children in the neighborhood formed a use and a particular construction of spatiality that functioned as a key signifier of social relations and, more specifically,modes social construct and symbolic identification with masculinity. Thus, I focused on gender constructions as a means of socialization and everyday strategy for local life.
Keywords: Gender; masculine identifications; socialization; ethnography with children; urban space